Pengaruh Leverage, Likuiditas, dan Profitabilitas terhadap Tax Avoidance dengan Ukuran Perusahaan sebagai Variabel Moderasi - Nabila Syifaa Azzahra Suwandi; David Pangaribuan; Panata Bangar Hasioan Sianipar (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research was conducted to test and analyze the influence of leverage, liquidity and profitability on tax avoidance, as well as the role of company size as a moderating variable. The research objects used in this research are industrial sector companies listed on the IDX in 2023, namely 63 companies. The sampling technique used in this research was purposive sampling, then data was obtained from 57 companies that passed the predetermined criteria. The results show that leverage has a negative effect and profitability has a positive effect on tax avoidance, while liquidity has no effect. Company size weakens the influence of leverage on tax avoidance, but does not moderate the influence of liquidity and profitability.